High-fracture-resistance aluminum oxide multilayer ceramic substrate and preparation method thereof

Through the composite treatment of copper powder, sodium feldspar powder and calcium feldspar powder and potassium dihydrogen phosphate molten salt treatment, the problem of insufficient flexural performance of alumina multi-layer ceramic substrates is solved, significantly improving its bending strength and fracture toughness, and is suitable for high-performance electronic equipment.

CN120554099AActive Publication Date: 2025-08-29HEBEI DINGCI ELECTRONIC TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511079570.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-04
Publication Date
2025-08-29
Estimated Expiration
2045-08-04

AI Technical Summary

Technical Problem

The alumina multilayer ceramic substrate has poor flexural resistance and is difficult to effectively resist crack propagation, which limits its application in miniaturized, highly integrated and high-frequency electronic devices.

Method used

Copper powder, soda feldspar powder and calcium feldspar powder are combined to form a densified surface layer by molten salt treatment of potassium dihydrogen phosphate. Combined with polyvinyl alcohol and sintering aid, the ratio of alumina and feldspar powder is regulated, and the bending strength and fracture toughness of the multi-layer ceramic substrate of alumina are improved.

Benefits of technology

The bending strength and fracture toughness of the alumina multi-layer ceramic substrate are significantly improved, so that its bending strength is increased to more than 462MPa and the fracture toughness is increased to more than 12.9MPa·m1/2, improving the flexural resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic substrates, and provides a high-fracture-resistance aluminum oxide multilayer ceramic substrate and a preparation method thereof. The high-fracture-resistance aluminum oxide multilayer ceramic substrate comprises the following components in parts by weight: 100 parts of composite aluminum oxide, 5-8 parts of a sintering aid, 3-5 parts of a dispersing agent, 5-8 parts of a binder and 70 parts of a solvent, the preparation method of the composite aluminum oxide comprises the following steps: A1, uniformly mixing aluminum oxide and copper powder, carrying out compression molding, and sintering to obtain a pre-compound; a2, dispersing polyvinyl alcohol in water, adding the pre-compound and feldspar powder, uniformly mixing, concentrating, drying, calcining, cooling and crushing to obtain composite aluminum oxide; the feldspar powder comprises albite powder and anorthite powder. According to the technical scheme, the problem of poor fracture resistance of the aluminum oxide multilayer ceramic substrate in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic substrates, and in particular to a highly flexural-resistant alumina multilayer ceramic substrate and a preparation method thereof. Background Art

[0002] Alumina multilayer ceramic substrates are widely used in electronic packaging, integrated circuits, and other fields due to their excellent thermal conductivity and chemical stability. However, as electronic devices move towards miniaturization, high integration, and high frequency, the market's performance requirements for ceramic substrates are becoming increasingly stringent.

[0003] Alumina, as the primary ceramic material for alumina ceramic substrates, has a direct impact on the performance advantages of alumina multilayer ceramic substrates due to its inherent properties. Alumina itself possesses high hardness and heat resistance, providing the ceramic substrate with mechanical support and high-temperature resistance. However, alumina itself exhibits defects such as high brittleness, surface defect sensitivity, and rapid crack propagation, resulting in its inability to effectively resist crack propagation when subjected to strong external stresses. Therefore, its direct use in ceramic substrates limits the improvement of the ceramic substrate's flexural strength. Currently, reinforcing phases such as silicon carbide and mullite can be introduced to improve alumina's ability to resist crack propagation by refining the grain size and adjusting the size. However, grain refinement and internal size adjustment are affected by multiple factors, such as sintering temperature and material type, making them difficult to achieve, making it difficult to improve the flexural strength of ceramic substrates.

[0004] Therefore, developing an alumina multilayer ceramic substrate can effectively improve its anti-bending performance, which plays an important role in improving the comprehensive performance of the alumina multilayer ceramic substrate and extending its service life. Summary of the Invention

[0005] The present invention provides a highly flexural-resistant alumina multilayer ceramic substrate and a preparation method thereof, which solves the problem of poor flexural-resistant alumina multilayer ceramic substrates in the related art.

[0006] The technical solutions of the present invention are as follows: The present invention provides a highly flexural-resistant alumina multilayer ceramic substrate comprising the following components in parts by weight: 100 parts of composite alumina, 5-8 parts of sintering aid, 3-5 parts of dispersant, 5-8 parts of binder, 70 parts of solvent; The preparation method of the composite alumina comprises the following steps: A1. Alumina and copper powder are mixed evenly, pressed into shape, and sintered to obtain a pre-composite; A2. Dispersing polyvinyl alcohol in water, adding the pre-composite and feldspar powder, mixing uniformly, concentrating, drying, calcining, cooling, and crushing to obtain composite alumina; The feldspar powder includes sodium feldspar powder and calcium feldspar powder.

[0007] As a further technical solution, the weight ratio of the aluminum oxide to the copper powder is 100:3~8, for example, it can be 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, preferably 100:3, 100:5, 100:8, and more preferably 100:5.

[0008] As a further technical solution, the weight ratio of the alumina to the feldspar powder is 20:2-7, for example, 20:2, 20:3, 20:4, 20:5, 20:6, 20:7, preferably 20:3-5; The weight ratio of the calcium feldspar powder to the sodium feldspar powder is 1.5 to 3:1, for example, 1.5:1, 2:1, 2.5:1, 3:1, preferably 1.5:1, 3:1, and more preferably 1.5:1.

[0009] In the highly flexural-resistant alumina multilayer ceramic substrate of the present invention, by regulating the content of alumina and feldspar powder, when the weight ratio of alumina to feldspar powder is 20:3-5, the flexural performance of the alumina multilayer ceramic substrate can be further improved, and its bending strength can be increased to 448-453 MPa.

[0010] As a further technical solution, during the pulverization, the composite alumina is pulverized to a particle size of 60 to 80 μm, for example, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, preferably 60 μm.

[0011] As a further technical solution, the amount of polyvinyl alcohol added is 3% to 6% of the weight of the alumina.

[0012] As a further technical solution, in step A1, during the sintering, the sintering temperature is 1100-1150° C. and the sintering time is 20-30 min in a nitrogen atmosphere; In step A2, the calcination temperature is 500-600° C. and the calcination time is 50-70 min.

[0013] In the highly flexural-resistant alumina multilayer ceramic substrate of the present invention, the pretreatment of alumina with copper powder is carried out in a nitrogen environment. The nitrogen environment can reduce oxidation of the copper powder and thereby reduce the obstruction of the oxide film on the copper powder wetting the alumina.

[0014] As a further technical solution, the preparation method of the composite alumina comprises the following steps: B1. Mixing aluminum oxide and copper powder uniformly, pressing into a shape, and sintering to obtain a pre-composite; B2. dispersing polyvinyl alcohol in water, adding the pre-composite and feldspar powder, mixing uniformly, concentrating, drying, calcining, cooling, and pulverizing to obtain a composite; B3. After melting potassium dihydrogen phosphate, add the composite, mix evenly, and cool to obtain composite alumina.

[0015] In the highly flexural-resistant alumina multilayer ceramic substrate of the present invention, copper powder, sodium feldspar powder and calcium feldspar powder are used to perform a composite treatment on the alumina, and then potassium dihydrogen phosphate molten salt is used for treatment. The relatively large potassium ions can partially replace the relatively small sodium ions in the sodium feldspar powder on the surface of the alumina, which can form surface plane extrusion to a certain extent, and the potassium ions in the potassium dihydrogen phosphate molten salt can penetrate into the pores of the surface calcium feldspar powder. After cooling, the molten salt exists in the surface pores in a solid form, thereby making the surface of the composite alumina more dense. This also reduces the shrinkage deformation of the composite alumina during the sintering process when the alumina multilayer ceramic substrate is prepared in the later stage, thereby further improving the bending strength of the alumina multilayer ceramic substrate, and at the same time, its fracture toughness is also improved to a certain extent.

[0016] As a further technical solution, the weight ratio of the potassium dihydrogen phosphate to the feldspar powder is 1:2.5~4.

[0017] In the highly flexural-resistant alumina multilayer ceramic substrate of the present invention, when the weight ratio of potassium dihydrogen phosphate to feldspar powder is 1:2.5-4, the bending strength and fracture toughness of the alumina multilayer ceramic substrate are improved better, and the bending strength of the alumina multilayer ceramic substrate can be further increased to above 462 MPa, and the fracture toughness can be increased to 12.9 MPa·m 1 / 2 above.

[0018] As a further technical solution, in step B3, when the mixing is uniform, the temperature is 400-450° C. and the time is 3-4 hours.

[0019] As a further technical solution, the sintering aid includes one or more of Y2O3, La2O3, and MgF2, preferably La2O3; The dispersant includes one or both of tributyl phosphate and polyethylene glycol, preferably polyethylene glycol; The binder comprises one or both of polyvinyl butyral and carboxymethyl cellulose, preferably polyvinyl butyral; The solvent includes one or both of ethanol and n-butanol, preferably ethanol.

[0020] The present invention provides a method for preparing a highly flexurally resistant alumina multilayer ceramic substrate, which comprises the following steps: S1. After mixing all the components evenly, ball milling is performed to obtain a casting slurry; S2, degassing the casting slurry, casting and drying it to obtain a green porcelain sheet; S3, punching, filling, printing, stacking, laminating, sintering, and cooling the green ceramic sheets to obtain the highly flexurally resistant alumina multilayer ceramic substrate.

[0021] As a further technical solution, when laminating, the number of layers is 40 to 45.

[0022] As a further technical solution, in step S3, during the sintering, the sintering temperature is 1300-1400° C. and the sintering time is 2-3 hours in a nitrogen atmosphere.

[0023] The working principle and beneficial effects of the present invention are: In the highly flexurally resistant alumina multilayer ceramic substrate of the present invention, copper powder, calcium feldspar powder, and sodium feldspar powder are used to composite alumina, thereby increasing the flexural strength of the alumina multilayer ceramic substrate and thereby improving the flexural performance of the alumina multilayer ceramic substrate. To reduce the impact of the alumina's inherent surface defects, such as its sensitivity to surface defects and rapid surface crack propagation, on the flexural performance of the ceramic substrate, the present invention first pre-treats the alumina with copper powder to improve its interfacial wettability. The pre-treated alumina is then composited with feldspar powder using polyvinyl alcohol, forming a non-expandable feldspar powder coating on the alumina surface. After calcination and cooling, the inner alumina layer contracts more readily than the outer feldspar powder layer, generating compressive stress within the feldspar powder coating. This compressive stress effectively restricts the propagation of cracks in the alumina, thereby improving the flexural performance of the alumina multilayer ceramic substrate. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0025] In the following examples and comparative examples, the average particle size of alumina is 10 μm; the purity of copper powder is 99.9%; the model of polyvinyl alcohol is PVA 1788; the average particle size of albite powder is 80 nm; the average particle size of calcium feldspar powder is 80 nm; the model of polyethylene glycol is PEG-1000; and the model of polyvinyl butyral is TB-20.

[0026] Example 1 The preparation method of composite alumina comprises the following steps: A1. Mix 100 parts of aluminum oxide and 3 parts of copper powder, press into shape, and sinter at 1100° C. for 30 minutes under a nitrogen atmosphere to obtain a pre-composite. A2. Disperse 3 parts of polyvinyl alcohol in 150 parts of water, add the above pre-composite, 4 parts of sodium feldspar powder and 6 parts of calcium feldspar powder, mix well, concentrate, dry, calcine at 500°C for 70 minutes, cool, and crush to obtain a composite alumina with a particle size of 60 μm; A method for preparing a highly flexurally resistant alumina multilayer ceramic substrate comprises the following steps: S1, 100 parts of composite alumina, 5 parts of La2O3, 3 parts of polyethylene glycol, 5 parts of polyvinyl butyral and 70 parts of ethanol were mixed uniformly, and then ball-milled to obtain a casting slurry; S2, degassing the casting slurry, casting and drying it to obtain a green porcelain sheet; S3. After punching, filling and printing the green ceramic sheets, 40 layers of green ceramic sheets are stacked and laminated. They are sintered at a sintering temperature of 1300° C. for 3 hours in a nitrogen atmosphere and cooled to obtain a highly flexurally resistant alumina multilayer ceramic substrate.

[0027] Example 2 The preparation method of composite alumina comprises the following steps: A1. 100 parts of aluminum oxide and 5 parts of copper powder were mixed evenly, pressed into a mold, and sintered at 1120° C. for 25 minutes under a nitrogen atmosphere to obtain a pre-composite. A2. Disperse 5 parts of polyvinyl alcohol in 150 parts of water, add the above pre-composite, 4 parts of sodium feldspar powder and 6 parts of calcium feldspar powder, mix well, concentrate, dry, calcine at 550°C for 60 minutes, cool, and crush to obtain a composite alumina with a particle size of 60 μm; A method for preparing a highly flexurally resistant alumina multilayer ceramic substrate comprises the following steps: S1, 100 parts of composite alumina, 6 parts of La2O3, 4 parts of polyethylene glycol, 6 parts of polyvinyl butyral and 70 parts of ethanol were mixed and ball-milled to obtain a casting slurry; S2, degassing the casting slurry, casting and drying it to obtain a green porcelain sheet; S3. After punching, filling and printing the green ceramic sheets, 40 layers of green ceramic sheets are stacked and laminated. They are sintered at a sintering temperature of 1350° C. for 2.5 hours in a nitrogen atmosphere and cooled to obtain a highly flexurally resistant alumina multilayer ceramic substrate.

[0028] Example 3 The preparation method of composite alumina comprises the following steps: A1. Mix 100 parts of aluminum oxide and 8 parts of copper powder, press into shape, and sinter at 1150° C. for 20 minutes under a nitrogen atmosphere to obtain a pre-composite. A2. Disperse 6 parts of polyvinyl alcohol in 150 parts of water, add the above pre-composite, 2.5 parts of sodium feldspar powder and 7.5 parts of calcium feldspar powder, mix well, concentrate, dry, calcine at 600°C for 50 minutes, cool, and crush to obtain a composite alumina with a particle size of 60 μm; A method for preparing a highly flexurally resistant alumina multilayer ceramic substrate comprises the following steps: S1, 100 parts of composite alumina, 8 parts of La2O3, 5 parts of polyethylene glycol, 8 parts of polyvinyl butyral and 70 parts of ethanol were mixed and ball-milled to obtain a casting slurry; S2, degassing the casting slurry, casting and drying it to obtain a green porcelain sheet; S3. After punching, filling and printing the green ceramic sheets, 40 layers of green ceramic sheets are stacked and laminated. They are sintered at a sintering temperature of 1400° C. for 2 hours in a nitrogen atmosphere and cooled to obtain a highly flexurally resistant alumina multilayer ceramic substrate.

[0029] Example 4 The only difference between this embodiment and embodiment 2 is that, in the preparation method of composite alumina in this embodiment, 6 parts of sodium feldspar powder and 9 parts of calcium feldspar powder are added.

[0030] Example 5 The only difference between this embodiment and embodiment 2 is that in the preparation method of composite alumina in this embodiment, 10 parts of sodium feldspar powder and 15 parts of calcium feldspar powder are added.

[0031] Example 6 The only difference between this embodiment and embodiment 2 is that in the preparation method of composite alumina in this embodiment, 14 parts of sodium feldspar powder and 21 parts of calcium feldspar powder are added.

[0032] Example 7 The preparation method of composite alumina comprises the following steps: B1. 100 parts of aluminum oxide and 5 parts of copper powder were mixed evenly, pressed into a mold, and sintered at a sintering temperature of 1120° C. for 25 minutes under a nitrogen atmosphere to obtain a pre-composite; B2. Disperse 5 parts of polyvinyl alcohol in 150 parts of water, add the above pre-composite, 10 parts of sodium feldspar powder and 15 parts of calcium feldspar powder, mix well, concentrate, dry, calcine at 550° C. for 60 min, cool, and crush to obtain a composite with a particle size of 60 μm; B3. After melting 10 parts of potassium dihydrogen phosphate, add the above-mentioned composite, mix at 400° C. for 4 hours, and cool to obtain composite alumina; A method for preparing a highly flexurally resistant alumina multilayer ceramic substrate comprises the following steps: S1, 100 parts of composite alumina, 6 parts of La2O3, 4 parts of polyethylene glycol, 6 parts of polyvinyl butyral and 70 parts of ethanol were mixed and ball-milled to obtain a casting slurry; S2, degassing the casting slurry, casting and drying it to obtain a green porcelain sheet; S3. After punching, filling and printing the green ceramic sheets, 40 layers of green ceramic sheets are stacked and laminated. They are sintered at a sintering temperature of 1350° C. for 2.5 hours in a nitrogen atmosphere and cooled to obtain a highly flexurally resistant alumina multilayer ceramic substrate.

[0033] Example 8 The only difference between this embodiment and embodiment 7 is that, in this embodiment, 8 parts of potassium dihydrogen phosphate are added.

[0034] Example 9 The only difference between this embodiment and embodiment 7 is that, in this embodiment, 6.25 parts of potassium dihydrogen phosphate are added.

[0035] Example 10 The only difference between this embodiment and embodiment 7 is that the preparation method of composite alumina is different in this embodiment, specifically: B1. 100 parts of aluminum oxide and 5 parts of copper powder were mixed evenly, pressed into a mold, and sintered at a sintering temperature of 1120° C. for 25 minutes under a nitrogen atmosphere to obtain a pre-composite; B2. Disperse 5 parts of polyvinyl alcohol in 150 parts of water, add the above pre-composite, 10 parts of sodium feldspar powder and 15 parts of calcium feldspar powder, mix well, concentrate, dry, calcine at 550° C. for 60 min, cool, and crush to obtain a composite with a particle size of 60 μm; B3. After melting 10 parts of potassium dihydrogen phosphate, add the above-mentioned compound, mix at 450° C. for 3 hours, and cool to obtain composite alumina.

[0036] Comparative Example 1 The only difference between this comparative example and Example 2 is that the preparation method of composite alumina is different in this comparative example, specifically: The preparation method of composite alumina comprises the following steps: 100 parts of aluminum oxide and 5 parts of copper powder were mixed evenly, pressed into shape, sintered at a sintering temperature of 1150° C. for 25 minutes under a nitrogen atmosphere, and crushed to obtain composite aluminum oxide with a particle size of 60 μm.

[0037] Comparative Example 2 The only difference between this comparative example and Example 2 is that the preparation method of composite alumina is different in this comparative example, specifically: The preparation method of composite alumina comprises the following steps: Disperse 5 parts of polyvinyl alcohol in 150 parts of water, add 100 parts of alumina, 6 parts of sodium feldspar powder and 4 parts of calcium feldspar powder, mix evenly, concentrate, dry, calcine at 550°C for 60 minutes, cool, and crush to obtain composite alumina with a particle size of 60 μm.

[0038] Comparative Example 3 The only difference between this comparative example and Example 2 is that the preparation method of composite alumina is different in this comparative example, specifically: The preparation method of composite alumina comprises the following steps: A1. 100 parts of aluminum oxide and 5 parts of copper powder were mixed evenly, pressed into a mold, and sintered at 1120° C. for 25 minutes under a nitrogen atmosphere to obtain a pre-composite. A2. Disperse 5 parts of polyvinyl alcohol in 150 parts of water, add the above pre-composite and 10 parts of sodium feldspar powder, mix well, concentrate, dry, calcine at 550°C for 60 minutes, cool, and crush to obtain composite alumina with a particle size of 60 μm.

[0039] Comparative Example 4 The only difference between this comparative example and Example 2 is that the preparation method of composite alumina is different in this comparative example, specifically: The preparation method of composite alumina comprises the following steps: A1. 100 parts of aluminum oxide and 5 parts of copper powder were mixed evenly, pressed into a mold, and sintered at 1150° C. for 25 minutes under a nitrogen atmosphere to obtain a pre-composite. A2. Disperse 5 parts of polyvinyl alcohol in 150 parts of water, add the above pre-composite and 10 parts of calcium feldspar powder, mix well, concentrate, dry, calcine at 550°C for 60 minutes, cool, and crush to obtain composite alumina with a particle size of 60 μm.

[0040] Experimental Example 1 Bending Strength Test The high-bending-resistance alumina multilayer ceramic substrate samples prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were subjected to a flexural strength test according to the three-point bending test method of GB / T 6569-2006 "Test Method for Flexural Strength of Fine Ceramics". The test results are shown in Table 1: Table 1 Bending strength test results

[0041] Compared to Comparative Examples 1-4, the flexural strength of the highly flexurally resistant alumina multilayer ceramic substrates prepared in Examples 1-10 was increased to over 423 MPa, indicating that the combined treatment of alumina with copper powder, sodium feldspar powder, and anorthite powder can increase the flexural strength and improve the flexural performance of the alumina multilayer ceramic substrate. Furthermore, compared to Example 5, the flexural strength of the highly flexurally resistant alumina multilayer ceramic substrates prepared in Examples 7-10 was further increased, indicating that the combined treatment of alumina with copper powder, sodium feldspar powder, and anorthite powder followed by treatment with potassium dihydrogen phosphate molten salt can further enhance the flexural performance of the alumina multilayer ceramic substrate.

[0042] Experimental Example 2 Fracture Toughness Test The high-flexural-resistance alumina multilayer ceramic substrate samples prepared in Examples 5 and 7 to 10 were tested for fracture toughness according to the method in GB / T 23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method". The test results are shown in Table 2: Table 2 Fracture toughness test results

[0043] Compared with Example 5, the fracture toughness of the highly flexural alumina multilayer ceramic substrates prepared in Examples 7 to 10 is improved, indicating that the fracture toughness of the alumina multilayer ceramic substrate can be improved by treating the alumina with copper powder, sodium feldspar powder, and calcium feldspar powder and then treating the alumina with potassium dihydrogen phosphate molten salt.

[0044] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. Highly flexural-resistant alumina multilayer ceramic substrate, characterized in that: The composition comprises the following components in parts by weight: 100 parts of composite alumina, 5-8 parts of sintering aid, 3-5 parts of dispersant, 5-8 parts of binder, 70 parts of solvent; The preparation method of the composite alumina comprises the following steps: A1. Alumina and copper powder are mixed evenly, pressed into shape, and sintered to obtain a pre-composite; A2. Dispersing polyvinyl alcohol in water, adding the pre-composite and feldspar powder, mixing uniformly, concentrating, drying, calcining, cooling, and crushing to obtain composite alumina; The feldspar powder includes sodium feldspar powder and calcium feldspar powder.

2. The highly flexural-resistant alumina multilayer ceramic substrate according to claim 1, characterized in that: The weight ratio of the aluminum oxide to the copper powder is 100:3-8.

3. The highly flexural-resistant alumina multilayer ceramic substrate according to claim 1, characterized in that: The weight ratio of the alumina to the feldspar powder is 20:2-7; The weight ratio of the calcium feldspar powder to the sodium feldspar powder is 1.5-3:

1.

4. The highly flexural-resistant alumina multilayer ceramic substrate according to claim 1, characterized in that: The added amount of the polyvinyl alcohol is 3% to 6% of the weight of the alumina.

5. The highly flexural-resistant alumina multilayer ceramic substrate according to claim 1, characterized in that: In step A1, during the sintering, the sintering temperature is 1100-1150° C. and the sintering time is 20-30 min in a nitrogen atmosphere; In step A2, the calcination temperature is 500-600° C. and the calcination time is 50-70 min.

6. The highly flexural-resistant alumina multilayer ceramic substrate according to claim 1, characterized in that: The preparation method of the composite alumina comprises the following steps: B1. Mixing aluminum oxide and copper powder uniformly, pressing into a shape, and sintering to obtain a pre-composite; B2. dispersing polyvinyl alcohol in water, adding the pre-composite and feldspar powder, mixing uniformly, concentrating, drying, calcining, cooling, and pulverizing to obtain a composite; B3. After melting potassium dihydrogen phosphate, add the composite, mix evenly, and cool to obtain composite alumina.

7. The highly flexural-resistant alumina multilayer ceramic substrate according to claim 6, characterized in that: The weight ratio of the potassium dihydrogen phosphate to the feldspar powder is 1:2.5-4.

8. The highly flexural-resistant alumina multilayer ceramic substrate according to claim 6, characterized in that: In step B3, when the mixing is uniform, the temperature is 400-450° C. and the time is 3-4 hours.

9. The highly flexural-resistant alumina multilayer ceramic substrate according to claim 1, characterized in that: The sintering aid includes one or more of Y2O3, La2O3, and MgF2; The dispersant includes one or both of tributyl phosphate and polyethylene glycol; The binder includes one or both of polyvinyl butyral and carboxymethyl cellulose; The solvent includes one or both of ethanol and n-butanol.

10. A method for preparing a highly flexurally resistant alumina multilayer ceramic substrate, for preparing the highly flexurally resistant alumina multilayer ceramic substrate according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. After mixing all the components evenly, ball milling is performed to obtain a casting slurry; S2, degassing the casting slurry, casting and drying it to obtain a green porcelain sheet; S3, punching, filling, printing, stacking, laminating, sintering, and cooling the green ceramic sheets to obtain the highly flexurally resistant alumina multilayer ceramic substrate.

Citation Information

Patent Citations

  • Flaky alumina and preparation method thereof

    CN101891226A

  • High temperature creep-resistant flake alumina porous ceramic used for LED lamp heat dissipation, and preparation method thereof

    CN105110772A

  • Efficient heat dissipation multilayer ceramic substrate and preparation method thereof

    CN119774988A

  • Alumina multilayer ceramic substrate and preparation method thereof

    CN120097716A

  • Dispersion-reinforced aluminium matrix-based composite material and method for production thereof

    RU2595080C1